Tools development for analysis and conceptual design of extractive and azeotropic distillation columns at finite reflux (2012)
In this work shortcut methods are developed for the conceptual design of azeotropic and extractive distillation. Three specific cases of azeotropic and extractive distillation are studied: single-feed homogeneous azeotropic distillation, extractive homogeneous distillation and single-feed heterogeneous distillation. To evaluate the process feasibility, to calculate design parameters and minimum energy by shortcut methods is the core of this work. Methods developed are based on the pinch concept and the use of mathematical tools for modeling the thermodynamic behavior. Continuation methods are used throughout the work in order to either devise or modify calculation algorithms that can be robust and useful for any kind of mixture. Finally, different mixtures with academic or industrial relevance were selected as case studies to demonstrate the applicability of conceptual design and shortcut methods in distillation process. Obtained results demonstrate that the use of conceptual design methods is an efficient way to avoid the trial and error design strategy carried out in simulators by engineers.